Economic Evaluation of Small Hydroelectric Generation Project which aims to both Global Warming Adaptation and Regional Economic Revitalization - Eiji Ohno; Ryuta Mori; Masafumi Morisugi; Hiroshi Sao (European Regional Science Association (ERSA), 2014)
Based on the international agreements after the Kyoto Protocol, some projects to reduce the greenhouse gas emission have been promoted even in Japan. Therefore, policies such as various regulations and introduction of the environmental tax have been discussed, so people will be asked for big burden. However, in many local cities, problems such as falling birth rate, aging, and stagnation of regional economy are important subjects, so it is hard to give the priority to the global warming prevention policy. In addition, in spite of abundance of natural resources such as forest, wind, water, and sunlight, the local city has a problem that the fund for the global warming prevention policy which utilizes these resources cannot be procured by financial difficulties. On the other hand, the renewable energy business with citizen participation will give the local community some effects. On the environment aspect, the carbon dioxide emission will be reduced by introducing the renewable energy. On the economy aspect, the local employment will be stimulated if the local contractor will construct the renewable energy system and maintain it. Therefore, there should be the renewable energy business which would achieve both the global warming prevention and the regional economic revitalization. Furthermore, through such business with citizen participation, the environmental activity of the local residents will be activated, and we can expect that the semi-public service will be improved and the satisfaction of the local residents will rise. In this paper, we propose a small hydroelectric generation project with citizen participation which includes not only donation to the project but also cooperation in the activity such as cleaning and patrols. And the project is evaluated economically based on the willingness to work (WTW) by using the contingent valuation method and the general equilibrium analysis. As a result, the WTW for the project has been estimated as a function of its various attributes; the revenue, the profit to the local community, and the reward to contributors. On the other hand, the revenue should vary with the number of contributors; where the number means the WTW. As for the profit to the local community and the reward to contributors, these are positioned as the policy variables. Therefore, by using our evaluation model, we will be able to evaluate various policies for the renewable energy business; for example, policies which make the revenue maximize, policies which make the social utility maximize, and so on.
Keywords: Q42; Q51; R13; 330; small hydro-electric generation; global warming prevention; regional economic revitalization; contingent valuation method; general equilibrium analysis